Spatial distribution of air temperature and air flow analysis in radiant cooling system using CFD technique - Rahul Khatri; Vaibhav Rai Khare; Hemant Kumar (Energy Reports, 2020)
This paper describes the air flow analysis and distribution of a radiant cooling system installed in a commercial building. Computational Fluid Dynamics (CFD) simulations using ANSYS were carried out to identify the thermal performance of the radiant cooling system. The calibration of simulated model was done using the actual data and a hypothetical case of conventional cooling system has been evaluated with the help of TRNSYS for comparative analysis. The CFD simulations were carried out to find the effect of the spatial distribution of air for the radiant system and the conventional system. It was recorded that a radiant cooling system maintains uniform air distribution and better average air temperature as compared to a conventional cooling system. Impact of thermal mass on the fluctuations of the temperature was also studied and it was identified that the higher thermal mass prevents high fluctuations in operative temperatures.
Keywords: 330; Building energy simulation; CFD; HVAC; Radiant cooling; Thermal mass; TRNSYS